Web-based decision system for effective process planning in network manufacturing environment - Varela, Maria Leonilde Rocha (2016)
Recent advancements in Information technology and pervasive applications of Web-enabled services wield a profound influence on manufacturing systems and in particular on distributed networked manufacturing environment. In this paper, a modelling schema is proposed for integrating a distributed feature-based design system to organize concurrent engineering activities effectively. Later, with developed Web based decision support tool the activities of manufacturing system are integrated. The managerial insights listed in this report, obtained from the analysis suggest that the developed methodologies and tool for networked manufacturing environment offers with a number of benefits such as high interoperability, openness, cost-efficiency, and production scalability.